Can harbor seals ( Phoca vitulina ) discriminate familiar conspecific calls after long periods of separation? - Varola, Mila; Verga, Laura; Sroka, Marlene Gunda Ursel; Villanueva, Stella; Charrier, Isabelle; Ravignani, Andrea (PeerJ, 2021)
International audience The ability to discriminate between familiar and unfamiliar calls may play a key role in pinnipeds’ communication and survival, as in the case of mother-pup interactions. Vocal discrimination abilities have been suggested to be more developed in pinniped species with the highest selective pressure such as the otariids; yet, in some group-living phocids, such as harbor seals ( Phoca vitulina ), mothers are also able to recognize their pup’s voice. Conspecifics’ vocal recognition in pups has never been investigated; however, the repeated interaction occurring between pups within the breeding season suggests that long-term vocal discrimination may occur. Here we explored this hypothesis by presenting three rehabilitated seal pups with playbacks of vocalizations from unfamiliar or familiar pups. It is uncommon for seals to come into rehabilitation for a second time in their lifespan, and this study took advantage of these rare cases. A simple visual inspection of the data plots seemed to show more reactions, and of longer duration, in response to familiar as compared to unfamiliar playbacks in two out of three pups. However, statistical analyses revealed no significant difference between the experimental conditions. We also found no significant asymmetry in orientation (left vs . right) towards familiar and unfamiliar sounds. While statistics do not support the hypothesis of an established ability to discriminate familiar vocalizations from unfamiliar ones in harbor seal pups, further investigations with a larger sample size are needed to confirm or refute this hypothesis.